Effectiveness for remission maintenance rate and safety of different rituximab regimens for treating anti-neutrophil cytoplasmic antibody-associated vasculitis in Japan: a J-CANVAS study - Chie Ogita; Kazuteru Noguchi; Jiro Takeuchi; Naoto Azuma; Satoshi Omura; Daiki Nakagomi; Yoshiyuki Abe; Masatoshi Kadoya; Naoho Takizawa; Atsushi Nomura; Yuji Kukida; Naoya Kondo; et al. (Immunological Medicine)
Rituximab (RTX) has been reported to effectively maintain remission in anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). In this multicenter study involving 57 patients who achieved remission after 24 weeks, we evaluated the effectiveness of RTX in maintaining remission in patients with AAV. Patients were divided into three groups based on RTX administration: continuous, induction phase-only, and maintenance phase-only groups. The continuous group had a remission maintenance rate after 48 weeks of treatment compared with the induction phase-only group (100% vs. 88.2%, p = 0.29). More patients in the continuous group received three or more RTX doses during the induction period (82.4% vs. 52.9%, p = 0.06), and this group had a lower incidence of infection (5.9% vs. 29.4%, p = 0.08). Compared with the maintenance-only group, the continuous group had a numerically higher proportion of patients in remission after 48 weeks of treatment (100% vs. 83.3%, p = 0.26) and a lower incidence of infection (5.9% vs. 50%, p = 0.04); however, the N in the maintenance phase was small and suspected to have low power. Regardless of the method of RTX administration (induction phase-only or continuous), administering RTX during the induction phase may be crucial for achieving remission.